Istigāśah and the Construction of Social Ethics: A Case Study of Jama'ah Mantab in Ogan Ilir, Indonesia - Romadhon Romadhon; Abdullah Idi; Abdurrahmansyah Abdurrahmansyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This article examines the role of istigāśah in shaping social ethics and collective morality through the study of the religious practices of the Jama’ah Mantab in the Ogan Ilir region, Indonesia. Istigāśah not only functions as a spiritual ritual, but also as a medium of moral transformation in the social life of the members. This research is a field research with a qualitative approach and phenomenological methods. Data were collected through participatory observation, in-depth interviews, and documentation of routine istigāśah activities. The analysis is carried out with reference to the theory of social constructionism, which emphasizes that social realities, including moral values, are formed through symbolic interaction and the process of construction of common meaning within religious communities. In addition, the theory of moral transformation is also used to explain the dynamics of ethical change in the members. The results of the study show that istigāśah plays a role in internalizing values such as patience, honesty, solidarity, and empathy, as well as strengthening collective awareness, social attachment, and moral identity. Thus, istigāśah not only strengthens individual spirituality, but also forms a more harmonious social order. This research contributes to the development of the study of social ethics and sociology of religion by emphasizing that collective religious practices such as istigāśah can be an effective instrument in building collective morality in society.